Spatial analysis of genetic clusters and epidemiologic factors related to wild poliovirus type 1 persistence in Afghanistan and Pakistan. - Amalia Mendes; Ari Whiteman; Kelley Bullard; Salmaan Sharif; Adnan Khurshid; Muhammad Masroor Alam; Muhammad Salman; Vanessa Ford; Taisha Blair; Cara C Burns; Derek Ehrhardt; Jaume Jorba; et al. (Public Library of Science (PLoS), 2022)
Following the certification of the World Health Organization Region of Africa as free of serotype 1 wild poliovirus (WPV1) in 2020, Afghanistan and Pakistan represent the last remaining WPV1 reservoirs. As efforts continue in these countries to progress to eradication, there is an opportunity for a deeper understanding of the spatiotemporal characteristics and epidemiological risk factors associated with continual WPV1 circulation in the region. Using poliovirus surveillance data from 2017-2019, we used pairwise comparisons of VP1 nucleotide sequences to illustrate the spatiotemporal WPV1 dispersal to identify key sources and destinations of potentially infected, highly mobile populations. We then predicted the odds of WPV1 detection at the district level using a generalized linear model with structural indicators of health, security, environment, and population demographics. We identified evidence of widespread population mobility based on WPV1 dispersal within and between the countries, and evidence indicating five districts in Afghanistan (Arghandab, Batikot, Bermel, Muhamandara and Nawzad) and four districts in Pakistan (Charsada, Dera Ismail Khan, Killa Abdullah and Khyber) act as cross-border WPV1 circulation reservoirs. We found that the probability of detecting WPV1 in a district increases with each armed conflict event (OR = 1·024, +- 0·008), level of food insecurity (OR = 1·531, +-0·179), and mean degrees Celsius during the months of greatest precipitation (OR = 1·079, +- 0·019). Our results highlight the multidisciplinary complexities contributing to the continued transmission of WPV1 in Afghanistan and Pakistan. We discuss the implications of our results, stressing the value of coordination during this final chapter of the wild polio virus eradication initiative.